1997
DOI: 10.2307/3870555
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Osmotic and Cold Stress Signal Transduction in Arabidopsis: Interactions and Convergence of Abscisic Acid-Dependent and Abscisic Acid-Independent Pathways

Abstract: To dissect genetically the complex network of osmotic and cold stress signaling, we constructed lines of Arabidopsis plants displaying bioluminescence in response to low temperature, drought, salinity, and the phytohormone abscisic acid (ABA). This was achieved by introducing into Arabidopsis plants a chimeric gene construct consisting of the firefly luciferase coding sequence (LUC) under the control of the stress-responsive RD29A promoter. LUC activity in the transgenic plants, as assessed by using in vivo lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
342
0
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(361 citation statements)
references
References 0 publications
11
342
0
8
Order By: Relevance
“…AtADH1 was reported to be a cold, dehydration, hypoxia, and ABA-inducible gene [52,53]. Regulation of the ADH1 gene in Arabidopsis by AtCBF2 is suggested by experiments, which alter accumulation of CBF2 [54][55][56] and overexpression of CBF2 [57]. Maruyama et al [17] suggested that the specific promoter elements regulated by DREB2 are ACCGAC, GTCGGT and CCGACT, while DREB1A/CBF3 regulated primarily ACCGAC.…”
Section: Gmdreb1a;2mentioning
confidence: 99%
“…AtADH1 was reported to be a cold, dehydration, hypoxia, and ABA-inducible gene [52,53]. Regulation of the ADH1 gene in Arabidopsis by AtCBF2 is suggested by experiments, which alter accumulation of CBF2 [54][55][56] and overexpression of CBF2 [57]. Maruyama et al [17] suggested that the specific promoter elements regulated by DREB2 are ACCGAC, GTCGGT and CCGACT, while DREB1A/CBF3 regulated primarily ACCGAC.…”
Section: Gmdreb1a;2mentioning
confidence: 99%
“…Some of these encode proteins responsible for the biosynthesis of hormones, such as abscisic acid (ABA), which can act as signaling molecules that amplify and spread the initial stress signal. Interestingly, different stresses as well as ABA treatment can change the expression of a common set of genes, indicating that stress responses are mediated in part by overlapping signaling pathways (Ishitani et al, 1997;Shinozaki and Yamaguchi-Shinozaki, 2000;Rabbani et al, 2003). However, these common signaling pathways might be activated in a different temporal and spatial manner by individual stresses (Xiong et al, 2002;Delessert et al, 2004;Kilian et al, 2007;Dinneny et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To cope with such unfavorable growth conditions, plants have developed unique defense mechanisms and processes for acclimation that enhance their tolerance to detrimental conditions. A number of genetic and cellular events that occur under such stress have been widely documented (Bray, 1997;Ishitani et al, 1997;Zhu, 2002). Diverse sets of genes induced by drought and/or salt stress have been identified recently with the aid of combined molecular and genetic approaches (Ingram and Bartels, 1996;Cushman and Bohnert, 2000;Seki et al, 2001Seki et al, , 2002Ozturk et al, 2002;Oono et al, 2003).…”
mentioning
confidence: 99%